The Impact of Web 2.0 Language Learning Applications on Students' Vocabulary Acquisition and Perception - Muluk, Safrul; Furqan, Furqan; Sulaiman, Muntasir; Maskur, Maskur; Mayastika, Kania (IJEE (Indonesian Journal of English Education), 2024)
The acquisition of vocabulary significantly impacts language learning since it serves as the foundation for developing linguistic abilities. As a result, instructors must provide students with a contextual framework and various media resources to help them build an extensive understanding of language usage. Using information and communication technology (ICT) in the classroom can maximise student learning by maximising their potential (Adisti, 2018). The Busuu language learning application is one of the online learning resources available. The researchers goal in this study is to examine at how the Busuu language learning application affects vocabulary acquisition among students in a vocational school in Aceh, Indonesia. A quantitative research approach was used, utilizing a survey questionnaire and experimental teaching. Purposive sampling was employed to select 30 students from the Business and Marketing class to participate in the research. The findings indicate that students, performance in acquiring new English vocabulary improved significantly following the intervention. The pre-test results, averaging 6.86, and the post-test, averaging 9.9, show a 3.03 improvement. The Busuu application also received favourable feedback from research participants, who found it to be enjoyable and educational.